The Play's the Thing: Loewald's Metaphors of the Theater and the Force-Field. Issue 1 (1st January 2018) - Brett, Elizabeth A.
ABSTRACT: I argue that "Psychoanalysis as an Art and the Fantasy Character of the Psychoanalytic Situation" is of immediate use to the analytic clinician. Its graphic metaphors of a force-field and a play provide experience-near descriptions of the therapeutic interchange. Building on his more widely known and theoretically dense model of the mother–infant matrix, Loewald uses the idea of a theatrical play to illustrate the externalization of fantasy action sequences in the scenarios played out in the transference and countertransference field. In the creation of their play, the patient and analyst become artist and medium for each other. I elaborate this latter idea by drawing on the work of Dobyns (1996), a contemporary poet. A poem creates a relationship with a reader by using metaphor to awaken experience and stimulate self-examination. In the clinical situation, the content of the associations and enacted object relations are metaphors revealing the underlying fantasy action sequences. A clinical vignette illustrates these ideas and the options for interpreting them in the therapeutic field (Ferro 2002).